2019
DOI: 10.1016/j.pscychresns.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

FMRI correlates of olfactory processing in typically-developing school-aged children

Abstract: Human olfactory processing is understudied relative to other sensory modalities, despite its links to neurodevelopmental and neurodegenerative disorders. To address this limitation, we developed a fast, robust fMRI odor paradigm that is appropriate for all ages and levels of cognitive functioning. To test this approach, thirty-four typically developing children aged 7-12 underwent fMRI during brief, repeated exposure to phenylethyl alcohol, a flower-scented odor. Prior to fMRI scanning, olfactory testing (odor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For example, a fast repetition time (TR < 1 second) combined with a short stimulation length (6‐second odor stimulation in a 20‐second block) was associated with more rapid increase of BOLD signal in the olfactory regions . A short total odor exposure time may prevent rapid adaptation in the primary olfactory areas . Nevertheless, these studies, including the current one, are based on group inference.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, a fast repetition time (TR < 1 second) combined with a short stimulation length (6‐second odor stimulation in a 20‐second block) was associated with more rapid increase of BOLD signal in the olfactory regions . A short total odor exposure time may prevent rapid adaptation in the primary olfactory areas . Nevertheless, these studies, including the current one, are based on group inference.…”
Section: Discussionmentioning
confidence: 84%
“…Obviously this happened despite the pulsed delivery of odors in the current study. It has been argued that in addition to a short task duration, the stimulation within runs (eg, in each block) is also important for a consistent activation across the primary (piriform) and secondary olfactory areas . For example, a fast repetition time (TR < 1 second) combined with a short stimulation length (6‐second odor stimulation in a 20‐second block) was associated with more rapid increase of BOLD signal in the olfactory regions .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, physiological factors such as respiration and metabolic status also influence the sensitivity for detecting differences between groups. Some approaches have been suggested to increase SNR regarding the odor stimulation paradigm, e.g., short odor stimulation time [ 23 , 24 ] rapid repetition time (< 1 s) during brain image acquisition [ 25 ] or task protocols applied (e.g. synchronization of the breathing cycle with odor stimulation) [ 23 ] In addition, sequential stimulation with increasing intensities of odor may potentially offset potential habituation effects [ 26 ] Moreover, the presently used odors were familiar food-related.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrated that odor-induced brain activation in the amygdala covaried with the participants’ odor sensitivity [ 23 ]. However, such correlation does not ensure the generalizability of the established relationship to out-of-sample individual subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactometer used in this experiment was built in the Instrument Development Laboratory at the University of Washington Center on Human Development (see Kleinhans et al., 2018, for more detail). The olfactometer design was based on Lorig, Elmes, Zald, and Pardo (1999), with a modification of the odorant cylinders/manifold and nosepiece.…”
Section: Methodsmentioning
confidence: 99%